Nilai-Nilai Edukatif dalam Tradisi Bibu Adat Masyarakat Dayak Bekidoh di Desa Engkode Kabupaten Sanggau - Firga, Yustinus Jacob Edelestal; Zakso, Amrazi; Purnama, Shilmy; Bahari, Yohanes; Sulistyarini, Sulistyarini (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to find out how educational values in the tradition of bibu adat of Dayak bekidoh community in Engkode Village, Sanggau Regency. The research method is qualitative research with a descriptive approach to create a description of the educational values ​​of the Dayak Bekidoh community in Engkode Village. The data collection techniques are observation, interviews and documentation techniques. Data analysis uses data reduction and data presentation and drawing conclusions. The research results show that (1) the traditional bibu tradition aims to unite male and female couples in a traditional way, asking for blessing from God (Akek Penompo) and the ancestors, as well as validating and confirming the couple's status in custom and in society. (2) There are four educational values ​​in the Dayak Bekidoh community in Enkode Village, namely: religious values, moral values, cultural values ​​and also social values. In the procession, this traditional bibu tradition involves God and ancestors. Educative values ​​are instilled through joint activities such as mutual cooperation, mutual assistance, mutual aid and cooperation between communities. and through the symbolic meaning of tools and food menus in this tradition which teaches honesty, empathy, responsibility, and the importance of maintaining harmony in household life.